2011
DOI: 10.1016/j.bbamem.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in transient receptor potential melastatin 6 mRNA stability caused by rapamycin in renal tubular epithelial cells

Abstract: Rapamycin, an inhibitor of mammalian target of rapamycin (mTOR), is used in treatments for transplantation and cancer. Rapamycin causes hypomagnesemia, although precisely how has not been examined. Here, we investigated the effect of rapamycin on the expression of transient receptor potential melastatin 6 (TRPM6), a Mg2+ channel. Rapamycin and LY-294002, an inhibitor of phosphatidilinositol-3 kinase (PI3K) located upstream of mTOR, inhibited epidermal growth factor (EGF)-induced expression of the TRPM6 protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
2
15
0
1
Order By: Relevance
“…This study demonstrated that TRPM6 activity was increased upon binding of EGF to EGFR, making EGF the first magnesiotropic hormone. The increased activity results from an increase in the mobility and cell-surface expression of TRPM6 [52]. These findings matched perfectly with earlier observations that certain EGFR-targeting chemotherapeutic agents cause hypomagnesaemia.…”
Section: Egfr Modulatorssupporting
confidence: 90%
“…This study demonstrated that TRPM6 activity was increased upon binding of EGF to EGFR, making EGF the first magnesiotropic hormone. The increased activity results from an increase in the mobility and cell-surface expression of TRPM6 [52]. These findings matched perfectly with earlier observations that certain EGFR-targeting chemotherapeutic agents cause hypomagnesaemia.…”
Section: Egfr Modulatorssupporting
confidence: 90%
“…In an in vitro study using NRK-52E cells derived from normal rat renal tubules, Ikari et al revealed that sirolimus reduces mRNA expression TRPM6 at the DCT via inhibition of EGF-induced increase in TRPM6 expression, presumably by reducing the stability of TRPM6 mRNA. 63 In contrast, in a study using male Wistar rats treated with rapamycin, da Silva et al reported increased TRPM6 expression. 64 The magnesiuric effect of rapamycin in the latter study was thought to be due to the primary downregulation of NKCC2 protein expression leading to magnesiuria, followed by a secondary compensatory response with increased DCT TRPM6 protein expression.…”
Section: Reduced Tal Reabsorptionmentioning
confidence: 89%
“…mTOR participates in this process in nonneuronal cells. For example, rapamycin decreases the steady-state level of collagen ( COL1A1 and COL1A2 ) mRNA in fibroblasts and destabilizes inducible nitric oxide synthase mRNA in astrocytes and transient receptor potential melastatin 6 in renal tubular epithelial cells [6870]. Whether mTOR stabilizes transcripts that are induced by status epilepticus remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%